Accountability and ideology: The case of a German university under the Nazi regime. (May 2020) - Detzen, Dominic; Hoffmann, Sebastian
This article studies accountability demands at an educational institution following extreme changes of societal conditions, as observed in Nazi Germany (1933–1945). We refer to the Handelshochschule Leipzig founded as the first free-standing business school in Germany to show how the Nazi doctrine made its way into this university, affecting academics on both the organizational and the individual levels. As political accountability became a dominant governance instrument, most academics submitted to this new accountability regime. They became subjects of accountability, who can only be understood by the norms that were imposed on them. The change in accountability demands created considerable challenges for individuals, and, ex post, it may be impossible to ascertain their moral attitudes and how they attempted to cope with ensuing ethical dilemmas.